PLoS Pathogens Issue Image | Vol. 2(4) April 2006 (PLOS Pathogens, 2006)
Granulobacter bethesdensisA colorized scanning electron micrograph of the novel human pathogen Granulobacter bethesdensis (see Greenberg et al).Image Credit: Image provided by David Dorward and Gary Hettrick, NIAID/Rocky Mountain Laboratories.